Inculcating Religious Moderation Values to Counter Radicalism in Islamic Junior Secondary School Students - Zaenal Abidin; Ulfatul Fitriana, Rizha (Edukasia Islamika : Jurnal Pendidikan Islam, 2021)
This study aims to reveal the rationale behind the radicalism prevention which includes some various efforts to prevent radicalism, and the results accomplished from such effort in Islamic junior secondary school students. This is significantly important because students at this school level are in their early adolescence phase who are very unstable, imitative, and aggressive making them vulnerable for being exposed to radicalism. This study employed a case study approach. Data were collected through in-depth interviews, observations, and documentation, which were then, analyzed using the interactive models of Miles, Huberman, and Saldana consisted of data condensation, data display, and conclusion drawing. This study suggested that radicalism prevention was driven by the deep concern of principals and teachers of madrasah over the rise of students who are exposed to radicalism. Madrasahs need to seriously internalizing religious moderation values to students so that they are resistant to radicalism. The values are internalized systemically and continuously involving the process of strengthening nationalism in daily routine and extracurricular activities, intensifying the counter-radicalization activities through Islamic Education and Civic Education, and developing the NU-Aswaja based curriculum. The values are at a certain level capable of strengthening their resistance to radicalism.